Preschool Education in China: The Research on Curriculum Design and Teaching Strategies (Asian Education Studies, 2022)
Here is a research paper that focuses on curriculum design and instructional research strategies for preschool education in China. In the existing perception, curriculum design is divided into two parts. On the one hand, macro-curriculum design is mainly to determine the basic concepts, basic values and curriculum structure of the curriculum. On the other hand, micro-curriculum design is mainly to design specific curriculum according to the macro-curriculum framework structure, and the products are put into teaching as curriculum standards and teaching materials. This paper conducts a preliminary research on the current research on curriculum design and teaching in preschool education in China through literature analysis method and makes a detailed plan for the subsequent research.